Decentralised Energy A Global Game Changer - Froggatt, Antony; Weiman, Jens (Ubiquity Press, 2020)
As the contribution of renewable energy increases to meet climate change objectives, so does the extent to which electricity is generated by individuals and communities, moving a centralised system to a more decentralised one, with associated system management and integration challenges. However, new digital and storage technologies are enabling local system management, and reducing the need for, and cost of, centralised planning. Creating the right regulatory environment is crucial, but it is especially challenging given the pace of technology change. This book describes the deploying renewable energy in selected countries and describes how each stage is affected by the regulatory and industrial environments, as gives examples of how new business models that enable greater penetration of renewables and more localised grid management and consumer engagement are being deployed.